A study on the: quality in construction of 'Projek Perumahan Rakyat Termiskin, (PPRT) case study: Desa Keda Tanjung Setul Pendang Kedah / Lathipah Ahmad - Ahmad, Lathipah (2010)
Houses are very important to mankind, but nowadays with the increase of current living cost, many poor people can not afford to buy houses. In order to solve the problem government had built housing program known as "Projek Perumahan Rakyat Teraiiskin" (PPRT) for poorest people. In Kedah this project was perform by Lembaga Kemajuan Wilayah Kedah (KEDA). There are certain condition and process for the applicants to receive the PPRT houses. Years by years this project have bring prosperous to many poor people who has no houses. But problem exist with the houses since the increasing of current construction cost, defects can easily seen in the houses. This may due to poor workmanship and low quality of material used to build the houses. So researches conducted have two pronged objectives which are, to identify the quality of PPRT project from physical aspect and to identify type of defects that can be found at PPRT houses. Research methodologies that are used are through using questionnaires that is distributed to residents in research area, interview with the officers responsible in handling the project and lastly using observation method. Finally conclusion and recommendations will be make based on the research result.